Multi-Criteria Decision-Making Techniques for Improvement Sustainability Engineering Processes Volume 2 - Zavadskas, Edmundas Kazimieras; Pamučar, Dragan; Stević, Željko; Mardani, Abbas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The success of any activity and process depends fundamentally on the possibility of balancing (symmetry) needs and their satisfaction. That is, the ability to properly define a set of success indicators. The application of the developed new multi-criteria decision-making (MCDM) methods can be eliminated or decreased by decision-makers' subjectivity, which leads to consistency or symmetry in the weight values of the criteria. In this Special Issue, 40 research papers and one review study co-authored by 137 researchers from 23 different countries explore aspects of multi-criteria modeling and optimization in crisp or uncertain environments. The papers propose new approaches and elaborate case studies in the following areas of application: MCDM optimization in sustainable engineering, environmental sustainability in engineering processes, sustainable multi-criteria production and logistics processes planning, integrated approaches for modeling processes in engineering, new trends in the multi-criteria evaluation of sustainable processes, and multi-criteria decision-making in strategic management based on sustainable criteria.